Pseudo‐allergic compounds screened from Shengmai injection by using high‐expression Mas‐related G protein‐coupled receptor X2 cell membrane chromatography online coupled with liquid chromatography and mass spectrometry. Issue 7 (2nd February 2021) - Sun, Wei; Wang, Saisai; Liang, Peida; Zhou, Huaxin; Zhang, Liyang; Jia, Qianqian; Fu, Jia; Lv, Yanni; Han, Shengli
Abstract: Adverse drug reactions of traditional Chinese medicine injection mainly manifested as pseudo‐allergic reactions. In the present study, ginsenoside Rd, Ro, and Rg3 were identified as pseudo‐allergic components in Shengmai injection by a high‐expression Mas‐related G protein‐coupled receptor X2 cell membrane chromatography coupled online with high‐performance liquid chromatography and mass spectrometry. Their pseudo‐allergic activities were evaluated by in vitro and in vivo assay. The three compounds were further found to induce pseudo‐allergic reaction through Mas‐related G protein‐coupled receptor X2. Therefore, we concluded that ginsenoside Rd, Ro and Rg3 may be potential allergens that cause pseudo‐allergic reactions. This study might be helpful for the safe use of Shengmai injection.